Depression and the self : meaning, control and authenticity - Browne, Tamara Kayali (USA Cambridge University Press, 2018)
"Depression is widely recognised as the leading disability worldwide. Though classified as a medical condition, depression also contains very personal and social aspects which are integral to the experience - as those who have experienced it know all too well. Drawing on research interviews with women who have experienced depression, this psychological study elucidates experiences of depression and the meanings attached to it. In so doing, Browne challenges current understandings of depression as a chronic and endogenous illness and stresses the importance of the perception of authenticity among depression sufferers. Written in plain language accessible to non-specialists, Depression and the Self argues that in depression, perceptions of control and the self are intertwined - and that this has important implications for diagnosis and recovery"--
Includes bibliographical references.
Keywords: Depression, Mental -- Popular works; Depression, Mental -- Popular works; PSYCHOLOGY / Clinical Psychology